EFFECT OF FINAL PROCESSING PRACTICES CARRIED OUT BY THE COFFEE COOPERATIVE SOCIETIES ON THE SUSTAINABILITY OF THE COFFEE INDUSTRY IN KENYA - Mwangi, Regina Wambui; Wachira, Dr. Anita Wanjugu; Mwenda, Dr. Lilian Karimi Mugambi; Mburu, Dr. David Kiarie (European Journal of Business and Strategic Management, 2017)
Purpose: The study sought to evaluate the effect of final processing practices carried out by the Coffee cooperative societies on the sustainability of the coffee industry in Kenya. Methodology: The study adopted descriptive research design. From a target population of 525 coffee cooperative societies in the East and West of the Rift valley, a sample size of 295 coffee cooperative societies was drawn using stratified random sampling where the response rate was 82.71 percent. The chair persons were the key respondents. A cross sectional survey was conducted where the questionnaires were the main data collection. Collected data was analyzed using descriptive and inferential statistics. Results: The results revealed that final processing practices and sustainability of the coffee industry are positively and significantly related. Using the regression of coefficient, final processing practices had a beta value of 0.264 with a t-value of 3.062 and p=0.002. Since p is <0.05, the null hypothesis was rejected at significant level of 0.05. This therefore implies that the final processing practices have a positive and significant effect on the sustainability of the coffee industry. Unique contribution to theory, practice and policy: The RBV theory can be used to transform the Kenyan coffee industry as it engages in value addition thereby producing unique end products which are competitive. To be able to boost the sustainability of the coffee industry, the study recommends that the government and the relevant policy makers in the coffee industry should come up with a variety of incentives that would encourage the adoption of the coffee value addition practices by the coffee cooperative societies in Kenya.